PEDAGOGICAL CONDITIONS FOR THE FORMATION OF INTEREST IN PHYSICAL CULTURE AMONG SCHOOLCHILDREN - Musayev Zarifjon Tursunaliyevich (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses physical education and sports activities are auxiliary means in the formation of a person's personality. They influence the preparation of young people for high-performance work and the defense of the motherland, the improvement of intellectual work, the education of high moral qualities, form their aesthetic tastes, feelings, ideals, needs.